2011
DOI: 10.1177/0269216310392102
|View full text |Cite
|
Sign up to set email alerts
|

Is oral morphine still the first choice opioid for moderate to severe cancer pain? A systematic review within the European Palliative Care Research Collaborative guidelines project

Abstract: The aim of this systematic review was to evaluate the evidence that oral morphine can be recommended as the first choice opioid in the treatment of moderate to severe cancer pain in updating the European Association for Palliative Care opioid recommendations. A systematic literature review was performed to update the 2007 Cochrane review 'Oral morphine for cancer pain'. The literature search was conducted on MedLine, EMBASE and Cochrane Central Register of Controlled Trials databases. The search strategy, limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 31 publications
(55 reference statements)
0
27
0
8
Order By: Relevance
“…A review of oral step III analgesic therapy including 62 trials in a total of 4241 patients showed that a mean pain score of about 3/10 was obtained in slightly less than one-third of the trials (18/62, 29%) [29]. A recent systematic review showed limited efficacy of opioids for relieving cancer pain, with substantial toxicity [32]. Furthermore, recent opioids such as oxycodone (Oxycontin ® , Oxynorm ® ) or hydromorphone (Sophidone ® ) were not more effective than morphine [32].…”
Section: Initial Efficacy Of High-dose Opioidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of oral step III analgesic therapy including 62 trials in a total of 4241 patients showed that a mean pain score of about 3/10 was obtained in slightly less than one-third of the trials (18/62, 29%) [29]. A recent systematic review showed limited efficacy of opioids for relieving cancer pain, with substantial toxicity [32]. Furthermore, recent opioids such as oxycodone (Oxycontin ® , Oxynorm ® ) or hydromorphone (Sophidone ® ) were not more effective than morphine [32].…”
Section: Initial Efficacy Of High-dose Opioidsmentioning
confidence: 99%
“…A recent systematic review showed limited efficacy of opioids for relieving cancer pain, with substantial toxicity [32]. Furthermore, recent opioids such as oxycodone (Oxycontin ® , Oxynorm ® ) or hydromorphone (Sophidone ® ) were not more effective than morphine [32]. Similarly, although several recommendations indicate that preference should be given to sustained-release forms, the six randomized trials that compared sustained-release to immediate-release opioids found no difference [33] in efficacy or adverse events, particularly addiction, both in noncancer pain and in cancer pain [34].…”
Section: Initial Efficacy Of High-dose Opioidsmentioning
confidence: 99%
“…In the light of the available scientific evidence that immediate-release oral morphine is both safe and effective as first-line treatment for severe pain (4,5);…”
Section: Considering the World Health Organization's Recommendation Tmentioning
confidence: 99%
“…Its short half-life allows frequent changes in dosing according to the individual needs. The low cost of morphine solution and immediate-release formulations and its potential availability are the major reasons for it to be recommended as a first-line opioid in the WHO Cancer Pain Relief Guidelines [15]. However, its narrow therapeutic index and severe side effects limit its therapeutic use.…”
Section: Introductionmentioning
confidence: 99%